Complications of Patellar Fracture Repair: Treatment and Results - Petrie, Jeffrey; Sassoon, Adam; Langford, Joshua (The Journal of Knee Surgery, 2013)
Open reduction and internal fixation (ORIF) of patellar fractures generally leads to good results; however, the potential for surgical complications exists. Nonunion, infection, posttraumatic arthritis, arthrofibrosis, symptomatic hardware, and extensor mechanism insufficiency have all been described following patellar ORIF, and the risk of their occurrence may be augmented by patient-, injury-, and treatment-related factors. When complications arise, advanced reconstructive techniques are often required for successful management. This review will report the incidence of the aforementioned complications, highlight risk factors contributing to their frequency, discuss treatment options, and present the reported results of selected treatment strategies from available literature.
Keywords: patellar fracture; patellar nonunion; hardware pain; complications